NUMBER HEAD TOGETHER TECHNIQUE: ITS USE TO IMPROVE INDONESIAN EFL STUDENTS’ READING ABILITY - Andri Maulana (English Department, STKIP PGRI Bandar Lampung, 2020)
The objective of this research is to improve students’ reading ability and learning activities through Number Head Together Technique at the tenth class of MA Hidayatul Mubtadi in Tulang Bawang Barat, Indonesia in 2017/2018. The subjects of this research consisted of thirty-one students. This research used classroom action research which was conducted in two circles. Each circle consisted of four steps: Identifying problems and planning action, implementing the action and observing or monitoring the action, reflecting the result of the observation, revising the plan for the following step. The data were collected through interviews, observation sheets, questionnaires, and tests. This research used both quantitative and qualitative techniques of data analysis. In the first cycle, the average score of class activities was Satisfactory. In the second cycle, the average score of class activities was increased. The significant improvement students’ reading ability shown from the average score of the first cycle was 69.80, there were 19 students or 61.29% who passed the Minimum Mastery Criterion, and the average score of the second cycle was 75,74, there were 25 students or 88.33% who passed the Minimum Mastery Criterion.